α-Glucosidase inhibition of lactone intermediates of the iminosugar deoxynojirimycin - Wai Haan, Y; Al-Bajalan, H; Eukun Sage, E; Elangovan, D; Liana Mat Yajit, N; Maisarah Sarizan, N; Zitzmann, N; Kiappes, J; Aishah Hasbullah, S; Hadiani Ismail, N; Mohamed Mackeen, M (Penerbit UTM Press, 2019)
α-Glycosidase enzymes hydrolyse α-glycosidic linkages and are involved in bodily processes such as the catabolism of glycans, intestinal digestion, and the degradation of glycoproteins. Various types of diseases which are caused by the failure of this enzyme to function properly can be treated through enzyme inhibition. The hydroxyethyl derivative of DNJ (Miglitol) is a clinical drug for the treatment of type 2 diabetes. Although the iminosugar D-deoxynojirimisin (D-DNJ) is an excellent micromolar glycosidase inhibitor, the α-glucosidase inhibition activity of D-DNJ lactone intermediates has yet to be reported. Therefore, the scalable synthesis of the D-DNJ intermediates 1,2-O-isopropylidene-α-D-glucurono-3,6-lactone (2), 1,2-O-isopropylidene-β-L-idurono-3,6-lactone (3) and 5-azido-5-deoxy-1,2-O-isopropylidene-α-D-glucurono-3,6-lactone (4) was carried out using D-glucuronolactone (1) as the starting material based on the method reported by Best et al. 2010 with some modification and subsequently, evaluated for anti-α-glucosidase activity. All products were characterised and identified by HPLC-ELSD, mass spectrometry (DI-ESI-MS) and NMR spectroscopy (via comparison of 1D 1H and 13C data with previously reported values). The inhibitory activity of compounds 1-4 towards α-glucosidase from Saccharomyces cerevisiae was evaluated using the p-nitrophenyl α-D-glucopyranoside substrate. Compound 3 showed 29.5% inhibition followed by 2 (21.4%), 1 (15.8%) and 4 (15.7%) compared to the positive control, quercetin (72.7%).